Development of a biobased superabsorbent polymer from recycled cellulose for diapers applications. (July 2019) - Lacoste, Clément; Lopez-Cuesta, José-Marie; Bergeret, Anne
Graphical abstract: Highlights: Cellulose from cardboards was successfully recovered through a totally chlorine free process. Carboxymethyl cellulose was synthetized from recovered cellulose with DS = 1.4. Carboxymethyl cellulose was crosslinked with citric acid to synthetized a biosuperabsorbent polymer.